Development of enterosorbents that can be added to food and water to reduce toxin exposures during disasters. Issue 6 (3rd June 2019) - Wang, Meichen; Hearon, Sara E.; Phillips, Timothy D.
Abstract: Humans and animals can be exposed to mixtures of chemicals from food and water, especially during disasters such as extended droughts, hurricanes and floods. Drought stress facilitates the occurrence of mycotoxins such as aflatoxins B1 (AfB1 ) and zearalenone (ZEN), while hurricanes and floods can mobilize toxic soil and sediments containing important pesticides (such as glyphosate). To address this problem in food, feed and water, we developed broad-acting, clay-based enterosorbents that can reduce toxin exposures when included in the diet. In this study, we processed sodium and calcium montmorillonite clays with high concentrations of sulfuric acid to increase surface areas and porosities, and conducted equilibrium isothermal analyses and dosimetry studies to derive binding parameters and gain insight into: (1) surface capacities and affinities, (2) potential mechanisms of sorption, (3) thermodynamics (enthalpy) of toxin/surface interactions and (4) estimated dose of sorbent required to maintain toxin threshold limits. We have also used a toxin-sensitive living organism ( Hydra vulgaris ) to predict the safety and efficacy of newly developed sorbents. Our results indicated that acid processed montmorillonites were effective sorbents for AfB1, ZEN and glyphosate, with high capacity and tight binding, and effectively protected hydra against individual toxins, as well as mixtures of mycotoxins.